REPRESENTATION OF FEMALE HEROES IN THE FOLK STORY OF PUTROE ALOEH: A STRUCTURAL AND SEMIOTIC ANALYSIS FROM ROLAND BARTHES' PERSPECTIVE - Fadila Pratiwi (JURNAL KONFIKS, 2025)
The Acehnese folktale “Putroe Aloeh” tells about the legendary value of female heroism in one of the provinces of Aceh, although it raises the narrative of female heroism, the representation of the character of Putroe Aloeh in the text is often overlooked from critical studies. In fact, there is a potential for hidden patriarchal ideology behind the heroic appearance. This study aims to explain the value of heroism, independence, the role of women presented in the Acehnese folktale “Putroe Aloeh”, the narrative structure of the story, revealing the denotation, connotation, and myth of female heroism formed through Roland Barthes' semiotic analysis. The method used in the study uses a qualitative approach with a descriptive design. Data collection techniques through documentation/text studies (oral transcripts and manuscripts). Data analysis techniques in the study by recording data, extracting and categorizing text studies structurally and semiotically from Roland Barthes' perspective. The results of the study show that the representation of female heroism in the Putroe Aloeh folktale is instrumental (a tool). Structurally, Putroe Aloeh plays the role of a Donor who has absolute power over magical assets (the "Flying Horse" and the "Areca Nut Tree") and tests male characters. This role is reinforced by a semiotic analysis that forms the myth that Putroe Aloeh's heroism stems from wealth and uniqueness (not physical actions), and is embodied as a ruler who determines negotiations. In conclusion, the ideology of the story acknowledges female power, but the narrative structure limits the role of power as a bridge for Malem Diwa to achieve her goals. Thus, the role of the highest act of courage lies with the male character. This study suggests the need for a critical review of folk narratives about heroic female figures to identify women's power as framed in a limited way in traditional literature.